Low serum concentrations of 25-hydroxyvitamin D in children and adolescents with systemic lupus erythematosus - O.A.B. Peracchi; M.T.R.A. Terreri; R.V. Munekata; C.A. Len; R.O.S. Sarni; M. Lazaretti-Castro; M.O.E. Hilário (Brazilian Journal of Medical and Biological Research, 2014)
We evaluated the concentrations of 25-hydroxyvitamin D [25(OH)D] in children and adolescents with juvenile systemic lupus erythematosus (JSLE) and associated them with disease duration and activity, use of medication (chloroquine and glucocorticoids), vitamin D intake, calcium and alkaline phosphatase levels, and bone mineral density. Thirty patients with JSLE were evaluated and compared to 30 healthy individuals, who were age and gender matched. Assessment was performed of clinical status, disease activity, anthropometry, laboratory markers, and bone mineral density. The 30 patients included 25 (83.3%) females and 16 (53.3%) Caucasians, with a mean age of 13.7 years. The mean age at diagnosis was 10.5 years and mean disease duration was 3.4 years. Mean levels of calcium, albumin, and alkaline phosphatase were significantly lower in patients with JSLE compared with controls (P<0.001, P=0.006, and P<0.001, respectively). Twenty-nine patients (97%) and 23 controls (77%) had 25(OH)D concentrations lower than 32 ng/mL, with significant differences between them (P<0.001). Fifteen patients (50%) had vitamin D levels <20 ng/mL and 14 had vitamin D levels between 20 and 32 ng/mL. However, these values were not associated with greater disease activity, higher levels of parathormone, medication intake, or bone mineral density. Vitamin D concentrations were similar with regard to ethnic group, body mass index, height for age, and pubertal stage. Significantly more frequently than in controls, we observed insufficient serum concentrations of 25(OH)D in patients with JSLE; however, we did not observe any association with disease activity, higher levels of parathormone, lower levels of alkaline phosphatase, use of medications, or bone mineral density alterations.